(X+12)+(4x-52)=90

Simple and best practice solution for (X+12)+(4x-52)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+12)+(4x-52)=90 equation:

Simplifying
(X + 12) + (4x + -52) = 90
Reorder the terms:
(12 + X) + (4x + -52) = 90
Remove parenthesis around (12 + X)
12 + X + (4x + -52) = 90
Reorder the terms:
12 + X + (-52 + 4x) = 90
Remove parenthesis around (-52 + 4x)
12 + X + -52 + 4x = 90
Reorder the terms:
12 + -52 + X + 4x = 90
Combine like terms: 12 + -52 = -40
-40 + X + 4x = 90
Solving
-40 + X + 4x = 90
Solving for variable 'X'.
Move all terms containing X to the left, all other terms to the right.
Add '40' to each side of the equation.
-40 + X + 40 + 4x = 90 + 40
Reorder the terms:
-40 + 40 + X + 4x = 90 + 40
Combine like terms: -40 + 40 = 0
0 + X + 4x = 90 + 40
X + 4x = 90 + 40
Combine like terms: 90 + 40 = 130
X + 4x = 130
Add '-4x' to each side of the equation.
X + 4x + -4x = 130 + -4x
Combine like terms: 4x + -4x = 0
X + 0 = 130 + -4x
X = 130 + -4x
Simplifying
X = 130 + -4x`